Uncovering Equity Consumer's Perceived Risk with Respect to Commodity Trading in Jaipur City Using Logistic Regression - Srivastava, Pooja Kudesia (Prabandhan: Indian Journal of Management, 2012)
Economy and inflation have become almost synonymous to each other, Investment decisions have become much more complex and less secured. Any Investment avenue which does not give returns more than the rate of inflation in a year's time will eventually end up depreciating the overall investment portfolio. Commodity trading offers an interesting avenue for spreading the risks. However, the equity consumers of major brokerage houses are observed to be averse to diversifying their portfolio. The following paper researches the various risks perceived by 100 High Net - worth Individuals in Jaipur city having a portfolio with leading brokerage houses of the city using logistic regression analysis.